Beyond Formality: Transforming FPIC into a Tool for Indigenous Empowerment - Aznannya, Siti Hatia (Yayasan Sinergi Kawula Muda, 2024)
This narrative review examines the integration of Indigenous rights within environmental legal frameworks, focusing on how Free, Prior and Informed Consent (FPIC) is conceptualized and implemented globally. The study aims to assess whether existing legal systems—both international and national—adequately ensure Indigenous communities' participation in environmental decision-making, particularly concerning extractive and infrastructure projects. Utilizing a narrative literature review method, we synthesized findings from international treaties, national legislations, and case studies from both developed and developing countries. The analysis was structured around the international legal foundations (e.g., UNDRIP, ILO 169), national legal adaptations, case studies involving extractive projects, and community-led strategies for environmental protection. The results show that although international frameworks provide strong normative guidance, national implementation is often inconsistent, constrained by political and economic interests. FPIC, while widely recognized, is frequently reduced to a procedural formality rather than serving as a tool for empowerment. Structural barriers, such as institutional weakness, legal ambiguity, and the dominance of economic paradigms, further erode Indigenous environmental rights. In contrast, countries that integrate legal pluralism and community-driven consultation show more promising outcomes. The study concludes that effective legal reform should prioritize participatory frameworks, enforceable FPIC mechanisms, and the institutionalization of customary knowledge. These findings have implications for policy reform and future research on environmental justice and Indigenous sovereignty.